Transforming the Elite : Black Students and the Desegregation of Private Schools - Purdy, Michelle A. (Book collections on Project MUSE., 2018)
"When traditionally white public schools in the South became sites of massive resistance in the wake of the Supreme Court's Brown v. Board of Education decision, numerous white students exited the public system altogether, with parents choosing homeschooling or private segregationist academies. But some historically white elite private schools opted to desegregate. The black students that attended these schools courageously navigated institutional and interpersonal racism, but ultimately emerged as upwardly mobile leaders. 'Transforming the Elite' tells this story. Focusing on the experiences of the first black students to desegregate Atlanta's well-known Westminster Schools and national efforts to diversify private schools, Michelle A. Purdy combines social history with policy analysis"--